2010
DOI: 10.1159/000315475
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Response to Pulmonary Rehabilitation in Idiopathic Pulmonary Fibrosis and Chronic Obstructive Pulmonary Disease

Abstract: Background: The benefits of pulmonary rehabilitation in chronic obstructive pulmonary disease (COPD) are well recognized. However, whether individuals with idiopathic pulmonary fibrosis (IPF) benefit is less clear. Objectives: To evaluate the effects of pulmonary rehabilitation in subjects with IPF and compare their responses with a group of COPD subjects who underwent an identical program. Methods: For- ty-five subjects with IPF and 45 age- and Medical Research Council grade-matched COPD subjects were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
133
3
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 66 publications
4
133
3
7
Order By: Relevance
“…Therefore, our data show a significant and clinically important improvement in all sub-and summary-scores of SF-36. Our observation is in concordance with some published studies [8,23,31,33], while others did not detect any influence of PR in HRQL [10,24,25]. NAJI et al [31] demonstrated in their group of ILD patients a significant reduction in anxiety and depression after completing PR.…”
Section: Figuresupporting
confidence: 93%
See 4 more Smart Citations
“…Therefore, our data show a significant and clinically important improvement in all sub-and summary-scores of SF-36. Our observation is in concordance with some published studies [8,23,31,33], while others did not detect any influence of PR in HRQL [10,24,25]. NAJI et al [31] demonstrated in their group of ILD patients a significant reduction in anxiety and depression after completing PR.…”
Section: Figuresupporting
confidence: 93%
“…We observed a small, statistically significant improvement of blood gas analysis and lung function parameters, which is in line with other published studies [10,23]. Although these improvements are statistically significant, their clinical relevance is probably negligible.…”
Section: Figuresupporting
confidence: 92%
See 3 more Smart Citations